THE LESS-INTERRESTED OF ISLAMIC BANK FOR ISSUING SUKUK: Factors and Recommendations - Taufik Awaludin; Irfan Syauqi Beik; Rifki Ismal (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2016)
This study attempts to identify dominant factors for banks to issue sukuk and emission features. Applying interviews and Analytic Network Process, this paper Found that the sub-elements which are dominant in influencing IB less interested in issuing sukuk, namely: averse selection/amount cost of fund (management), investment rating companies (investor), the results of using sukuk funds (regulation) and profitability condition (finance). Meanwhile, the sub-elements which are dominant in determining the features of the issuance of sukuk are: macroeconomic condition (emission values), expectations of investors (return)), the contract and the structure of sukuk (collateral), managing mismatch (period), and company liquidity (payment term). The method used in this reseach is the Analytic Network Process (ANP). This study will identify the aspects of emission factors and features.